Ageing in Puducherry, South India: An overview of morbidity profile - Bharati, Dharamvir Ranjan (Medknow Publications & Media Pvt Ltd, 2011)
BACKGROUND: The geriatric health problems are related to chronic disease as a result of increasing life expectancy. OBJECTIVE: This study was undertaken to assess the health problems of the elderly in Puducherry. MATERIALS AND METHODS: This cross-sectional study was carried out on 214 elderly persons from the age group of 60 years and above using a pre-designed and pre-tested questionnaire that addressed the disease magnitude in comparison with the socioeconomic variables. RESULTS: Overall, 43% of the participants were diabetic, 47.7% hypertensive, 86% anemic and 68.2% visually impaired. All the morbidities were noted to be higher in the 70–79 years age group. Diabetes was significantly higher in participants from urban areas, with family history and increasing waist–hip ratio, but significantly lower in the below poverty line areas. Hypertension risk was significantly higher among females, among those leading sedentary life, those eating vegetarian food, those addicted to tobacco and with abdominal obesity. Anemia was significantly lower among urban vegetarians. Overweight and obese were noted in 31% of the participants, and were higher in females (87.5%). Rural residence, female sex, living in joint family, literacy, sedentary life style, decreasing per capita income and decreasing body mass index (BMI) were significantly associated with visual impairment. CONCLUSION: This study highlights the burden of health problems of elderly individuals in South India.